Highly pure 1, 3‐propanediol: Separation and purification from crude glycerol‐based fermentation. Issue 8 (9th June 2015) - Wang, Shizhen; Qiu, Longhui; Dai, Hongfei; Zeng, Xiaofei; Fang, Baishan
Abstract : A new separation and purification process was developed for recovering 1, 3‐propanediol (1, 3‐PD) from crude glycerol‐based fermentation broth with high purity. The downstream process integrated chitosan flocculation, activated carbon decolorization, fixed bed cation exchange resin adsorption, and vacuum distillation. Breakthrough curves were measured considering the effect of sample concentration, flow rate, temperature, and resin stack height. Yoon–Nelson model was proposed to fit the fixed bed adsorption. The characteristic column parameters were calculated. Optimal condition for adsorption was 1, 3‐PD, 30.0 g/L; flow rate, 1.00 mL/min; stacking height, 30.0 cm; and temperature, 298 K. Ethanol‐water (75%, 1 mL/min) was used as eluent to separate 1, 3‐PD and glycerol with 95.3% 1, 3‐PD elution rate. After vacuum distillation, the overall purity and yield of 1, 3‐PD were 99.2% and 80.8% in the purification process, respectively. This is a simple and efficient downstream strategy for 1, 3‐PD purification.